Вплив мелатоніну на морфологічний стан м’яких тканин пародонту при їх експериментальному запаленні - Лабунець, А.І.; Тюпка, Т.І.; Лар’яновська, Ю.Б. (Таврический медико-биологический вестник, 2012)
В работе приведены результаты морфологического исследования мягких тканей пародонта крыс с экспериментальным гингивитом без лечения и при применении мелатонина. Установлено, что мелатонин препятствует развитию экспериментального гипертрофического гингивита у 40% крыс, а у 60% животных уменьшает выраженность его признаков. При остром альтеративном гингивите мелатонин значительно ускоряет процесс заживления. This research presents the results of morphological investigation of periodontal soft tissues of rats with experimental gingivitis without treatment and after the application of melatonin. Found out that melatonin prevents the development of experimental hypertrophic gingivitis in 40% of the rats and reduces the severity of his symptoms in the rest 60% of the animals. In acute alterative gingivitis melatonin significantly accelerates the healing process.